2017
DOI: 10.1155/2017/8793278
|View full text |Cite
|
Sign up to set email alerts
|

A Noninvasive Score Model for Prediction of NASH in Patients with Chronic Hepatitis B and Nonalcoholic Fatty Liver Disease

Abstract: Aims. To develop a noninvasive score model to predict NASH in patients with combined CHB and NAFLD. Objective and Methods. 65 CHB patients with NAFLD were divided into NASH group (34 patients) and non-NASH group (31 patients) according to the NAS score. Biochemical indexes, liver stiffness, and Controlled Attenuation Parameter (CAP) were determined. Data in the two groups were compared and subjected to multivariate analysis, to establish a score model for the prediction of NASH. Results. In the NASH group, ALT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Yang et al found that the serum CK-18 levels might be a risk factor for non-alcoholic steatohepatitis (NASH), chronic hepatitis C (CHC), and chronic hepatitis B (CHB) (all P < 0.05) through conducting a meta-analysis of eight case-control studies (20). Some reports also showed that the plasma levels of CK-18 M30 were associated with the progression of non-alcoholic steatohepatitis (NASH) in non-alcoholic fatty liver disease (NAFLD) patients (21,22). Recently, the associations between serum levels of CK-18 M30 and the progression of the chronic HBV infections were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al found that the serum CK-18 levels might be a risk factor for non-alcoholic steatohepatitis (NASH), chronic hepatitis C (CHC), and chronic hepatitis B (CHB) (all P < 0.05) through conducting a meta-analysis of eight case-control studies (20). Some reports also showed that the plasma levels of CK-18 M30 were associated with the progression of non-alcoholic steatohepatitis (NASH) in non-alcoholic fatty liver disease (NAFLD) patients (21,22). Recently, the associations between serum levels of CK-18 M30 and the progression of the chronic HBV infections were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern entered into our calculator consisted of abnormal levels of AST, ALT, AP, GGT associated with hyperlipidemia, obesity, and abnormal glucose metabolism (diabetes mellitus). Existing noninvasive models and scores combine clinical data (age, degree of obesity and diabetes, family history, AST:ALT ratio > 1), measures of elasticity and blood test variables (pointers of collagen metabolism, cell death (M30 CK-18), insulin resistance (adiponectin and resistin), or oxidative stress markers (thioredoxin, lipid peroxides), but have still not reached a wide clinical acceptance [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…A number of noninvasive score models were applied to identify NASH among patients with CHB. In a relatively small study with 64 CHB patients, Liang et al found that elevated serum level of CK18M30, higher CAP scores, and elevated fasting plasma glucose level were all independent risk factors for NASH [ 81 ]. Subsequently, a logistic regression model combining CK-18 M30, CAP, fasting plasma glucose, and HBV DNA level was established for diagnosis of NASH in CHB patients.…”
Section: Current and Novel Serum Biomarkers For Nafldmentioning
confidence: 99%